The role of fatwa (Islamic legal opinion) to Islamic banks and other financial institutions: a myth or reality in the Nigerian and Malaysian contexts? - Arifin, Mahamad; Abdullah, Mohamad Asmadi; Chiroma, Magaji (Ocerint International Organization Center of Academic Research, 2014)

(untitled)
Nowadays, Islamic banking having succeeded in guaranteeing the safety of customer’s wealth worldwide has stepped into tackling the arising issues within the banking sector. The main objective of the banking system is to ensure the true compliance with the principles of Islamic commercial jurisprudence through the effective means of supervision. The supervision is supposed to have been carried out by Islamic experts in a manner which effective and binding verdicts could be issued but a lot of challenges have been faced. The Islamic advisory board in an Islamic financial institution has been used for long as a collective fatwa issuing body saddled with the responsibility of ensuring the shari’ah compliance. However, involvement of technocrats therein coupled with some bureaucracies; and as well as lack of a suitable legal framework and enabling environment in support of its operation, have been causing a grievous injury to the system in recent times most especially in the Modern Muslim countries where shari’ah is applied side-by-side with other legal systems. In fact, such factors have resulted to lack of an effective legal framework on Islamic financial activities. It is against this backdrop that the paper has been jointly looked at the practices in Nigeria and Malaysia with a view to ascertaining the level playing ground for the performance of their shari’ah advisory bodies. In the end, the paper revealed that the Malaysian Islamic financial model is a reality compared to other countries in the world. Hence, the Malaysian model is expected to be suitable and relevant to the Nigerian system. Thus, the paper suggests among other things that generally, the Federal Government of Nigeria should adopt the Malaysian model of Islamic financial system; 2 specifically, the paper suggests that the Government in collaboration with Central Bank (CBN) should facilitate the amendment of the relevant legislation such as the Constitution of Nigeria, Bank and Other Financial Institution Act (BOFIA) and CBN Act/Regulations in order to pave way for enacting a suitable Islamic financial regulatory framework; and the Government should therefore enact a distinctive Islamic financial regulatory framework that can independently regulate for the Islamic financial activities in the country.